(untitled) (Revista Apotheke, 2022)
Concerned with the formation of subjectivity, this article seeks to reflect on the nomadic practices in the experiments carried out in a Teaching Internship in the Digital Art discipline of the Visual Arts course at the State University of Maringá (UEM). From a selfie, the students were encouraged to manipulate the photographs in editing software (such as Photoshop) inspired by the artistic processes of drag. This proposal starts from a rhizomatic approach to the curriculum, allowing it to be crossed by issues brokered by its outside. Thus, we bring to this discussion the concepts of nomadic figurations, a kind of political map that allows us to understand the processes of contemporary subjectivation, and faciality, a control machine that, through the formation of a face, inserts us into closed territories of experience. The manipulation of digital images, in addition to the coercive processes of body control, is used in our proposal as a practice of the self with the ability to organize nomadic movements for the formation of a more libertarian subjectivity.